The brown fiber phenotype in cotton line SA-40 is linked to a missing Ty3-like retrotransposon upstream of the GhTT2_A07 - Pinnika, Ganesh; Thyssen, Gregory N.; Madison, Crista A.; Li, Ping; Fang, David D.; Naoumkina, Marina; Hinchliffe, Doug J. (Frontiers in Plant Science, 2025)
IntroductionThe naturally brown colored fibers of some cottons exist in varying shades of brown. Linkage analyses have revealed up to six individual loci (Lc1–Lc6) for brown color and suggested a separate genetic basis for each color value of fibers. It was previously reported that the brown color and flame-retardant (FR) properties of Lc1 fibers resulted from an upstream inversion mutation that highly upregulates the GhTT2_A07 gene and, consequently, the entire phenylpropanoid pathway. However, the genes responsible for the coloration and FR of other brown cotton fibers remained undetermined.MethodsIn the current study, we used a previously uncharacterized SA-40 germplasm that produces rust-brown cotton. An F2 mapping population derived from the cross of SA-40 and TM-1 was used in an association mapping study to elucidate the genetics of SA-40 rust-brown fiber color and FR. Results and discussionThe rust-brown locus was mapped to GhTT2 on chromosome A07 (GhTT2_A07). Comparison of the upstream sequence of GhTT2_A07 between TM-1 and SA-40 revealed the absence of a Ty3-like LTR retrotransposon in the SA-40 line. No remnants of the LTR retrotransposon in the SA-40 indicated that the retrotransposon insertion did not happen in that line. However, all investigated white cotton lines in this study displayed the presence of the LTR retrotransposon upstream of GhTT2_A07. Transcript analysis showed that the absence of retrotransposon upstream of GhTT2_A07 was associated with higher expression of this gene, but at lower levels than previously reported for the upstream inversion mutation in the MC-BL line, where the retrotransposon has been removed by structural rearrangement. Our finding suggests that the value of brown coloration in Lc1 fibers is directly controlled by the expression level of GhTT2_A07, with higher expression levels resulting in darker fibers.